Pediatric Aplastic Anemia and Refractory Cytopenia: A retrospective analysis assessing outcomes and histomorphologic predictors - Forester, Craig M. (Am J Hematol, 2015)
Pediatric acquired aplastic anemia (AA) is a bone marrow disorder that is difficult to distinguish from inherited bone marrow failure syndromes and hypocellular refractory cytopenia of childhood (RCC). Historically, patients with hypocellular RCC have been given the diagnosis of AA. To assess the clinical and histologic distinction between RCC and AA, we performed a retrospective analysis of 149 patients previously diagnosed with AA between 1976-2010. We evaluated event free survival (EFS), overall survival (OS), response rates to immunosuppressive therapy, treatment-related toxicities and clonal evolution. The 5-year EFS and OS were 50.8%±5.5% and 73.1%±4.7%, respectively. Patients with very severe AA had worse OS compared to patients with severe and moderately severe AA. Seventy-two patients had diagnostic pathology specimens available for review. Three pediatric hematopathologists reviewed and reclassified these specimens as AA, RCC or Other based on 2008 WHO Criteria. The concordance between pathologists in the diagnosis of AA or RCC was modest. RCC was associated with a trend towards improved OS and EFS and was not prognostic of immunosuppression therapy treatment failure. There was a low rate of clonal evolution exclusively associated with moderately severe AA. Our findings indicate that a diagnosis of RCC is difficult to establish with certainty and does not predict outcomes, calling into question the reproducibility and clinical significance of the RCC classification and warranting further studies.